The Use of Androgen Deprivation Therapy in Combination With Radiation for Localized Prostate Cancer - Anderson, Eric M.; McBride, Sean M. (Frontiers in Urology, 2022)
Context: The combined use of androgen deprivation therapy (ADT) and radiotherapy in the initial treatment of intermediate and high risk prostate cancer is well established. Objectives: To review Level 1 evidence and post hoc analyses from prospective studies to determine the benefit for the addition of ADT to curative local therapies in prostate cancer and provide suggestions for future combinatorial trials in localized disease. Evidence Acquisition: We used PubMed to identify randomized controlled trials that compared curative therapy alone to curative therapy with androgen deprivation therapy. For critical questions for which randomized data was unavailable, we used studies that relied on post-hoc analyses from prospective randomized trials in an attempt to provide substantive answers. Evidence Synthesis: There is strong and unequivocal evidence that variable length ADT in combination with curative dose radiotherapy improves biochemical recurrence free survival, cause-specific survival (CSS), and overall survival in intermediate and high risk prostate cancer. Evidence Summary: ADT should be a component of treatment for most men with unfavorable intermediate and high risk prostate cancer receiving curative dose radiotherapy